A Bi-objective A* minimizing travel times and failure rates - Troncoso, Sergio; Montero, Elizabeth; Menares, Franco (LACCEI, 2024)
Routing problems are present in much activities in modern cities. These problems not only aim to minimize transportation costs and times, they also consider objectives that depend on time itself. These issues tend to be highly complex, and current solution methods require a lot of effort or are able to only deliver sub-optimal solutions. This research proposes a bi-objective algorithm based on BOA* to tackle the bi-objective asymmetric TSP. TDBOARR is aimed to minimize both, traveling times and rejection rates within the urban logistics landscape of Santiago de Chile. We analyze the performance of our approach comparing their results with a gurobi implementation of the mathematical model. TDBOARR shows being efficient finding the Pareto front extreme solutions, but unable to find most of central solutions.